Nucleotide sequence of the bean strain of southern bean mosaic virus() - Othman, Yasmin (Virology, 1995)
The genome of the bean strain of southern bean mosaic virus (SBMV-B) comprises 4109 nucleotides and thus is slightlyshorter than those of the two other sequenced sobemoviruses (southern bean mosaic virus, cowpea strain (SBMV-C) and rice yellow mottle virus (RYMV)). SBMV-B has an overall sequence similarity with SBMV-C of 55% and with RYMV of 45%. Three potential open reading frames (ORFs) were recognized in SBMV-B which were in similar positions in the genomes of SBMV-C and RYMV. However, there was no analog of SBMV-C and RYMV ORF 3. From a comparison of the predicted sequences of the ORFs of these three sobemoviruses and of the noncoding regions, it is suggested that the two SBMV strains differ from one another as much as they do from RYMV and that they should be considered as different viruses.